53 Survival and oncological outcomes in the elderly patients with endometrial carcinoma. (13th November 2020) - Shoraka, M; Kennedy, S; Carbajal Mamani, S; Cardenas Goicoechea, J
Abstract : Introduction: Endometrial cancer is the most common gynecological malignancy in developed countries and about 50% of patients are at age 70 or older at the time of diagnosis. Data is limited in the elderly as they are under-represented in clinical trials. The aim of our study is to evaluate the survival and oncological outcomes of elderly with endometrial carcinoma at an academic center. Methods: IRB-approved retrospective cohort study. Inclusion criteria consisted of age greater than 70 at the time of diagnosis with endometrial cancer who underwent surgery from January 2013 to November 2019 and with at least 6 months of follow up. Data collection included demographics, peri-operative outcome, and mortality. Results: A total of 121 patients met the inclusion criteria. The median age was 75 (range 70–91). The median follow-up was 31 months (range 1–87 month). Median overall survival was 76 months (95% CI 68–84 months). There was a significant difference between median overall survival among different races (79 months for White vs 62 months for Non-Whites). There was a significant difference between median overall survival of those with low grade tumor vs high grade (79 months vs 70; p=0.033), and stage 1 vs 2 and 3 (79 months vs 29 vs 28; p<0.001). Conclusions: Survival in elderly with endometrial carcinoma is much lower when compared to the general population especially with high grade or advanced stage disease. They are more likely to receive suboptimal treatment due to their health condition. Further clinical studies will give us the opportunity to develop treatment guidelines to improve outcomes.